Anesthetic management of patients with carnitine deficiency or a defect of the fatty acid β-oxidation pathway: A narrative review. Issue 7 (18th February 2022) - Yu, Ho Kyung; Ok, Seong-Ho; Kim, Sunmin; Sohn, Ju-Tae
Abstract : Abstract: Carnitine is essential for the transport of long-chain fatty acids from the cytoplasm to the mitochondrial matrix. The carnitine shuttle transports long-chain fatty acylcarnitine to the mitochondrial matrix. Subsequently, long-chain fatty acyl CoA, which is split from long-chain fatty acylcarnitine by carnitine palmitoyltransferase II, undergoes fatty acid β-oxidation. Acetyl CoA is produced from long-chain fatty acyl CoA via fatty acid β-oxidation and aids in the synthesis of adenosine triphosphate via the tricarboxylic acid cycle and electron transport chain. In addition, in the fasting state, it leads to ketone body production in the liver and glucose production via gluconeogenesis. However, patients with compromised fatty acid β-oxidation, owing to carnitine deficiency as well as defects in carnitine transport and the fatty acid β-oxidation pathway, develop hypoglycemia, cardiomyopathy, arrhythmia, and hypotonia. These conditions are attributed to the accumulation of released fatty acids and acylcarnitine. This review aimed to shed light on the anesthetic management of patients with compromised fatty acid β-oxidation undergoing various surgeries by assessing relevant case reports associated with fatty acid β-oxidation disorder in PubMed. Pre-anesthetic and intraoperative evaluation should include monitoring of glucose and carnitine levels and specific cardiac tests, such as echocardiography. Considering that propofol is dissolved in 10% long-chain fatty acids, propofol infusion should be avoided because of increased long-chain fatty acid loading in patients with compromised fatty acid β-oxidation. Thus, anesthesia using opioids (remifentanil and fentanyl), midazolam, dexmedetomidine, etomidate, and non-depolarizing neuromuscular blocking agents would be appropriate in such patients.